Interdependency of Aid Effectiveness and Good Governance - Mubazi, John Kigongo E. (Consilience, 2016)
The spirit of this article is to offer a fresh perspective related to the future of aid as a way of informing the ongoing discourse on development assistance to the benefit of policy makers and key stakeholders. It suggests that aid deployment ought to change in such a way as to improve governance and has shown where and how. We explore governance’s focus as well as the World Bank dimensions. Under focus, we concentrate on the transparency of government, the simplicity of procedures, accountability and responsibility, the need to fight against corruption, individual freedom and collective expression, and independence of the legal system. For the World Bank dimensions, the concentration is on: voice and accountability, political stability and the absence of violence, government effectiveness, regulatory quality, rule of law, and control of corruption. With respect to regulation and corruption, we address whether to use market-based or regulatory measures, possible policy instruments, implementation issues, and difficulties and problems. Under possible policy instruments, mandatory policy instruments, voluntary agreements, compliance instruments, and precautionary measures are explored. Implementation issues include introductory matters, costs, free riding and voluntary agreement and compliance. In addition, we examine difficulties associated with distributional issues, compensation, regulatory capture phenomenon, and the effect on innovation. Regarding corruption, we examine its definition, state capture versus conventional corruption, corrupt acts, forms of corruption, hypothetical causes of corruption, some analytical points, theoretical consequences, unbinding bribery, incidence of corruption, fraud, and control measures.